(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The study explores effective vocabulary learning strategies for young learners. The research was conducted at an educational center in Tashkent, Uzbekistan, focusing on young children, in particular. The results revealed that traditional oral memorization is no longer effective for long-term vocabulary retention. In contrast, bodily memorization contributed to improving students’ spelling accuracy despite having little effect on word comprehension. Active engagement, including the use of various games, cards, and daily conversations with these words, was the most effective approach for young learners to improve their vocabulary skills. The findings highlight the importance of the teacher’s role in finding effective ways and combining them into one so that their young students do not struggle with vocabulary learning.